Multilayered cultural identity and the perception of the self - Gomzina, Irina (2012)
This qualitative study examines the reciprocal relationship between a person’s multilayered cultural identity (MCI) and the concept of self (CoS), that is presented purely on a theoretical level and encompasses various theories. Nowadays, in an increasingly globalising world, it is not enough to merely look at a national, ethnic or other type of identity. It is important to realise that there are different layers in an identity that one can view themselves through. The ways an individual perceives themselves through their multicultural background can also be different. This thesis helps identify the ways a person can see themselves. The thesis also attempts to explain the varied nature of one’s self-perception, and the ways in which multilayered cultural identity can be manifested through self-perceiving. The way the literature review was conducted was through a partial approach to scope literature available on the topic for this study. In the process of examining the phenomenon, views of various authors have been presented on this subject. As a result of the comparison and analysis of different theories, it appears the term ‘multilayered cultural identity’ does not, in fact, exist in the modern literature. Instead, it is often used as ‘multicultural identity’ (MI).